2022
DOI: 10.3390/min12010104
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Acoustic Emission Waveforms Induced by Hydraulic Fracturing of Coal under True Triaxial Stress in a Laboratory-Scale Experiment

Abstract: Hydraulic fracturing (HF) is an effective technology to prevent and control coal dynamic disaster. The process of coal hydraulic fracturing (HF) induces a large number of microseismic/acoustic emission (MS/AE) waveforms. Understanding the characteristic of AE waveforms’ parameters is essential for evaluating the fracturing effect and optimizing the HF strategy in coal formation. In this study, laboratory hydraulic fracturing under true triaxial stress was performed on a cubic coal sample combined with AE monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Fitting Equation HM Cp = 0.48095p −2.87622 WY 1 C p = 0.60954p −2.47003 WY 2 C p = 0.22574p −3.66777…”
Section: Coal Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Fitting Equation HM Cp = 0.48095p −2.87622 WY 1 C p = 0.60954p −2.47003 WY 2 C p = 0.22574p −3.66777…”
Section: Coal Samplementioning
confidence: 99%
“…Coal permeability is an important parameter that affects the flow of coalbed gas and the efficiency of coalbed gas 2 of 16 extraction. Many relevant experiments and theoretical and numerical simulations regarding the factors influencing coal permeability have reached important conclusions [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…By capturing the AE energy events of loading and unloading specimens and infrared monitoring anomalies, the energy evolution characteristics of the model during the entire loading process were quantitatively analyzed. Li et al [9] conducted hydraulic fracturing (HF) tests under true triaxial stress on threedimensional coal samples in the laboratory and studied the time variation of injection pressure curves and AE waveform parameters at diferent stages through AE-monitoring technology. Te results showed that the characteristics of the AE waveform parameters well refect the growth behavior of coal HF.…”
Section: Introductionmentioning
confidence: 99%